The Role of The Global Financial Reporting Standards (GRI) in Enhancing Accounting Disclosure of Sustainability in Iraqi Companies - Yasir Mohamaad, Adnan (Journal of Economics and Administrative Sciences, 2025)
The research aims to identify the role of Global Financial Reporting Standards (GRI) in enhancing accounting disclosure of sustainability in Iraqi companies, by relying on the four global financial reporting standards, which include: the economic axis (GRI 200), the environmental axis (GRI 300), the social axis (GRI 400 and the general indicators (GRI 102),  the research sample represented an interantional companies listed on the Iraq Stock Exchange, namely: Al-Khatam Company and Asiacell Company. In order to analyse the results, the content and disclosure survey of the data and reports published in the Iraq Stock Exchange was employed. The accounting disclosure of sustainability was selected relying on the disclosed quantitative data. A set of indicators was chosen that are considered indicators for sustainability disclosure, which provide the most important indicators of disclosure of the dimensions of sustainability that can be addressed and studied within the Iraqi environment. Data from a sample of the two referred companies within the communications sector were analysed for the period (2021-2023). The hypotheses were tested using the regression method and the structural modelling method. The research concludes that the most important of which are: Financial Reporting Standards (GRI) contribute to increasing the level of transparency and credibility in financial reports related to sustainability, as they provide a clear framework for providing financial and non-financial information that helps investors and stakeholders evaluate the sustainable performance of companies. Among the most important recommendations of the research: Supporting companies listed on the Iraq Stock Exchange that adopt initiatives related to reporting accounting disclosure in achieving sustainability by several means to ensure their sustainability and continuity.